2022
DOI: 10.1186/s40359-022-00933-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of time perspectives and self-control on well-being and ill-being during the COVID-19 pandemic: A multiple mediation model

Abstract: Background A growing body of evidence indicates that the outbreak of COVID-19 has had a significant influence on individuals’ cognition, emotion, and psychological health. This study aims to explore the effect of the association between time perspectives and self-control on the well-being and ill-being among college students in China during the COVID-19 pandemic. Methods We conducted an online survey involving 1,924 participants in mainland China d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Notably, the recently published study by Zong and colleagues [42] also confirmed the significant role of the future and present hedonistic perspective on the association between perceived adverse COVID-19 impact and self-control, well-being, and ill-being. Interestingly, the findings indicated that the positive impact of having a future time perspective depends on the context, e.g., individuals under severe stress experience negative emotions and anxiety despite their high future time perspective.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Notably, the recently published study by Zong and colleagues [42] also confirmed the significant role of the future and present hedonistic perspective on the association between perceived adverse COVID-19 impact and self-control, well-being, and ill-being. Interestingly, the findings indicated that the positive impact of having a future time perspective depends on the context, e.g., individuals under severe stress experience negative emotions and anxiety despite their high future time perspective.…”
Section: Discussionmentioning
confidence: 63%
“…It is also positively related to self-regulation and goal setting [ 41 ] and is a positive predictor of academic achievement at school and university levels [ 23 ]. Future-oriented individuals are able to accurately formulate their future goals and anticipate the future implications of current decisions and behaviors [ 42 ], which is associated with resilience to distractors and the ability to wait for deferred rewards. These traits imply that future-oriented individuals have high self-esteem, intrinsic motivation to learn, and a strong sense of mastery.…”
Section: Discussionmentioning
confidence: 99%
“…Further study indicates that adolescent SVA may also be a result of stress and dissatisfaction with basic psychological needs [ [86] , [87] , [88] ]. According to the "compensatory loss hypothesis", being confined to their homes during the COVID-19 pandemic further reduces emotional regulation and SC [ 89 ], and adolescents may resort to "pathological" forms of addiction such as short videos [ 75 ], thereby increasing the likelihood of addiction during this period [ 90 , 91 ].compensation [ 75 ], thereby increasing the odds of addiction during this period [ 90 , 91 ]. If adolescents' SC can be improved, it may reduce SVA behaviour [ 92 ].…”
Section: Discussionmentioning
confidence: 99%